2007
DOI: 10.1007/s10067-006-0513-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant status in men with Behçet’s disease

Abstract: Behçet's disease (BD) is a chronic, progressive disorder that affects many systems of the body including the eye. The aim of this study was to assess whether the increase in oxidative stress in the affected tissues is reflected by lipid peroxidation and to check for alterations in antioxidants and antioxidant enzyme activities in patients with BD. Erythrocyte antioxidant potential (AOP), glutathione (GSH) and GSH-dependent enzymes (glutathione peroxidase (GSH-Px), glutathione reductase (GRD) and glutathione-S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…Ceruloplasmin (CP) produced by hepatocytes is an acute phase protein and has antioxidant characteristics (Gutteridge et al 1985). It has been reported that the activity of CP increases in patients with BD (Kose et al 1995;Taysi et al 2002).…”
Section: Measurement Of the Total Antioxidant Statusmentioning
confidence: 99%
“…Ceruloplasmin (CP) produced by hepatocytes is an acute phase protein and has antioxidant characteristics (Gutteridge et al 1985). It has been reported that the activity of CP increases in patients with BD (Kose et al 1995;Taysi et al 2002).…”
Section: Measurement Of the Total Antioxidant Statusmentioning
confidence: 99%
“…18 It has been shown that Mn-SOD genotypes containing the variant A allele were found to be associated with a 1.5-fold increased risk of breast cancer compared with those with the homozygous wild-type genotype (Mn-SOD VV). 17 Taysi et al 7 found that erythrocyte SOD activities were increased in BD compared to healthy controls whereas the other antioxidant enzymes, glutathione S transferase, catalase, and GPx were decreased. In another study, which investigated the oxidant-antioxidant status in whole blood from BD and controls, GPx was found to be decreased similarly to the previous paper.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from several studies suggests that neutrophils from patients with BD generate high levels of ROS and then this stress causes endothelial cell lysis in vitro. [3][4][5] On the other hand, different data reported in the literature show a variation for the activities of antioxidant enzymes in BD: erythrocyte superoxide dismutase (SOD) activity was found to be increased, 4,6,7 unchanged, 8 and decreased, 5,9 glutathione reductase activity was found to be increased, 7 catalase, glutathione reductase and glutathione peroxidase (GPx) activities were found to be decreased, [5][6][7][8][9] and ultimately, erythrocyte catalase activity was found to be unchanged 4 in BD patients.…”
mentioning
confidence: 99%
“…6 Serum MDA levels have been reported to be higher in patients with active and inactive ocular BD, and non-ocular BD compared to the control group. 7 Studies have also found increased MDA levels in patients with active disease than those inactive disease. 8 Furthermore, highly elevated serum MDA in patients with BD is an evidence of increased lipid peroxidation during the active stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The active ocular and nonocular BD groups were found to have significantly elevated ESR levels compared to the inactive ocular BD group. 7 When neutrophils and macrophages are stimulated by pathogens, cytokines and other inflammatory mediators such as C-reactive protein (CRP), are released from granules into the cytoplasm and they play a major role in destroying phagocytosed materials. CRP and ESR levels are sensitive markers of inflammation and reflect the activity of BD.…”
mentioning
confidence: 99%